EFL Slow Learners’ Perception in Speaking with Authentic Multimedia Assisted Language Learning - Ryani Yulian; Ufi Ruhama'; Putri Yuli Utami (Universitas Negeri Makassar, 2022)
The proliferation of assisted technology has been widely used in language learning, but this should be able to accommodate inclusive language learning which has become an important issue in today’s English language teaching and the higher education landscape in Indonesia. This study examined the perception of EFL slow learners in terms of the integration of an inclusive technology with authentic multimedia assisted language learning (AMALL). It discovered the impact of authentic multimedia assisted language learning on their speaking performance. This study also analysed the benefits of this technology perceived by the students. A mixed-method sequential exploratory was employed to examine students’ perception of EFL slow learners in speaking performance. A sample of 30 EFL learners was selected purposively to participate in this study. The study also examined the impact of this application by comparing the results of pre-test and post-test of the students’ speaking performance based on the analytic oral language-speaking rubric namely speaking, fluency, structure, and vocabulary. The findings of the study show that students perceived authentic multimedia assisted language learning provides some advantages in terms of usefulness, easiness, and effectiveness for speaking skill. There was also an improvement in speaking performance